Endothelin-1, over-expressed in SOD1G93A mice, aggravates injury of NSC34-hSOD1G93A cells through complicated molecular mechanism revealed by quantitative proteomics analysis - Zhang, Yingzhen; Chen, Lin; Li, Zhongzhong; Li, Dongxiao; Wu, Yue; Guo, Yansu (Frontiers in Cellular Neuroscience, 2022)
Endothelin-1 (ET-1), a secreted signaling peptide, is suggested to be involved in multiple actions in various tissues including the brain, but its role in amyotrophic lateral sclerosis (ALS) remains unknown. In this study, we detected the expression changes as well as the cellular localization of ET-1, endothelin A (ET-A) and endothelin B (ET-B) receptors in spinal cord of transgenic SOD1-G93A (TgSOD1-G93A) mice, which showed that the two ET receptors (ET-Rs) expressed mainly on neurons and decreased as the disease progressed especially ET-B, while ET-1 expression was up-regulated and primarily localized on astrocytes. We then explored the possible mechanisms underlying the effect of ET-1 on cultured NSC34-hSOD1G93A cell model. ET-1 showed toxic effect on motor neurons (MNs), which can be rescued by the selective ET-A receptor antagonist BQ-123 or ET-B receptor antagonist BQ-788, suggesting that clinically used ET-Rs pan-antagonist could be a potential strategy for ALS. Using proteomic analysis, we revealed that 110 proteins were differentially expressed in NSC34-hSOD1G93A cells after ET-1 treatment, of which 54 were up-regulated and 56 were down-regulated. Bioinformatic analysis showed that the differentially expressed proteins (DEPs) were primarily enriched in hippo signaling pathway-multiple species, ABC transporters, ErbB signaling pathway and so on. These results provide further insights on the potential roles of ET-1 in ALS and present a new promising therapeutic target to protect MNs of ALS.